Lack of robustness of hydrological models: a large-sample diagnosis and an attempt to identify hydrological and climatic drivers - L. Santos; V. Andréassian; T. O. Sonnenborg; G. Lindström; A. de Lavenne; A. de Lavenne; C. Perrin; L. Collet; L. Collet; G. Thirel (Hydrology and Earth System Sciences)
The transferability of hydrological models over contrasting climate conditions, also identified as model robustness, has been the subject of much research in recent decades. The occasional lack of robustness identified in such models is not only an operational challenge – since it affects the confidence that can be placed in projections of climate change impact – it also hints at possible deficiencies in the structures of these models. This paper presents a large-scale application of the robustness assessment test (RAT) for three hydrological models with different levels of complexity: GR6J, HYPE and MIKE SHE. The dataset comprises 352 catchments located in Denmark, France and Sweden. Our aim is to evaluate how robustness varies over the dataset and between models and whether the lack of robustness can be linked to some hydrological and/or climate characteristics of the catchments (thus providing a clue as to where to focus model improvement efforts). We show that, although the tested models are very different, they encounter similar robustness issues over the dataset. However, models do not necessarily lack robustness in the same catchments and are not sensitive to the same hydrological characteristics. This work highlights the applicability of the RAT regardless of model type and its ability to provide a detailed diagnostic evaluation of model robustness issues.